2002
DOI: 10.1016/s0014-5793(02)03441-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of novel phosphorylation sites in Cx43 in rat primary granulosa cells

Abstract: The gap junctional intercellular communication mediated by Cx43 plays indispensable roles in both germ line development and postnatal folliculogenesis. In this study, we focused on the e¡ect of follicle-stimulating hormone (FSH) on the Cx43 protein in rat primary granulosa cells and found that FSH stimulation elevated the phosphorylation in addition to the protein level of Cx43. Serine residues in the carboxyl-terminal region were exclusively phosphorylated in this system and we identi¢ed Ser365, Ser368, Ser36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…We previously found that FSH accelerated trafficking of Cx43 and accumulation of this protein i n g a p j u n c t i o n a l p l a q u e s a c c o m p a n y i n g phosphorylation in rat granulosa cells [40]. We further identified Ser365, Ser368, Ser369, and Ser373 as major sites of phosphorylation, and revealed the significance of serine phosphorylation in Cx43-mediated channel activity [16]. Namely, when all four serine residues were substituted with alanine, Cx43 appeared to lose dye transfer activity.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We previously found that FSH accelerated trafficking of Cx43 and accumulation of this protein i n g a p j u n c t i o n a l p l a q u e s a c c o m p a n y i n g phosphorylation in rat granulosa cells [40]. We further identified Ser365, Ser368, Ser369, and Ser373 as major sites of phosphorylation, and revealed the significance of serine phosphorylation in Cx43-mediated channel activity [16]. Namely, when all four serine residues were substituted with alanine, Cx43 appeared to lose dye transfer activity.…”
Section: Discussionmentioning
confidence: 70%
“…We previously found that recombinant Cx43-CT could be phosphorylated in vitro using rat granulosa cell lysate, and the sites of phosphorylation were identical to those observed in vivo [16]. We, therefore, expressed and purified 6x Histidinetagged Cx43-CT (Fig.…”
Section: Phosphorylation Of Cx43 In Vitromentioning
confidence: 65%
See 2 more Smart Citations
“…serines 365, 368, 369 and 373) in response to folliclestimulating hormone (FSH), probably at least partially through a PKA mechanism ( Fig. 1 and Table 1) (Yogo, Ogawa, Akiyama, Ishida, & Takeya, 2002). As shown in Table 1, there is experimental evidence that Cx43 can be phosphorylated on at least 12 of the 21 serines and two of the tyrosines of the cytoplasmic tail region (amino acids 250-382).…”
Section: Casein Kinase 1 (Ck1) and Other Kinasesmentioning
confidence: 97%